Digitalization of healthcare system of Kazakhstan - Bayeshova, M.U.; Omarov, A.M. (Bulletin of the Karaganda University. Mathematics Series, 2019)
The article is devoted to the development of digital technologies in the field of healthcare of Kazakhstan. The process of automation of a medical institution hospital is considered. The functionality of the developed information system and the prospects for the implementation of this system in this area are described. The developed information system allows it to accumulate the medical and statistical information in the databases of the hospital and use in practice, automates the management of the hospital workflow. The capabilities of the system consist in registering patients in a hospital, maintaining an electronic medical history and obtaining complete statistical reports. The patient’s electronic medical history contains his personal data, diagnoses, recommended procedures and medications. The introduction of information and communication technologies in the health sector will improve the quality of care and significantly speed up the work of staff.